Myosteatosis, but not Sarcopenia, Predisposes NAFLD Subjects to Early Steatohepatitis and Fibrosis Progression - Hsieh, Yun-Cheng; Joo, Sae Kyung; Koo, Bo Kyung; Lin, Han-Chieh; Lee, Dong Hyeon; Chang, Mee Soo; Park, Jeong Hwan; So, Young Ho; Kim, Won (Clinical gastroenterology and hepatology, 2023)
Sarcopenia and myosteatosis are associated with advanced nonalcoholic fatty liver disease (NAFLD). However, muscle alterations in early stage NAFLD remain unclear. Patients with nonalcoholic fatty liver (NAFL) or early nonalcoholic steatohepatitis (NASH) without significant fibrosis were selected from a prospective biopsy-proven NAFLD cohort (N = 338). The skeletal muscle index and mean muscle attenuation (MA) were measured using abdominal fat computed tomography at the third lumbar vertebra level. Severe myosteatosis was defined as the lowest quartile of sex-stratified MA values. Patients with early NASH (n = 87) had lower MA (45.61 ± 6.45 vs 47.48 ± 5.85 HU; P = .028) than patients with NAFL (n = 251) but a similar skeletal muscle index. Patients with more severe lobular inflammation and hepatocellular ballooning had lower MA (P = .003 and P = .041, respectively). The severe myosteatosis prevalence was higher in early NASH than in NAFL (33.3% vs 21.1%; P = .029). Patients with severe myosteatosis were more likely to have early NASH in multivariable analysis adjusted for age, sex, and metabolic factors (odds ratio, 2.45; 95% confidence interval (CI), 1.24–4.86), which was maintained after adjustment for visceral fat amount (odds ratio, 2.44; 95% CI, 1.22–4.89). During a median 29-month follow-up, 170 patients underwent repeated transient elastography. Fibrosis progression—an increase in liver stiffness measurement >2 kPa or second liver stiffness measurement ≥7 kPa—was found in 28 and 31 individuals. Severe myosteatosis was significantly associated with fibrosis progression after adjustment for various confounders (hazard ratio, 2.49; 95% CI, 1.15–5.40 and hazard ratio, 2.09; 95% CI, 1.01–4.34 for different fibrosis progression definitions). Severe myosteatosis is significantly associated with early NASH and fibrosis progression in early stage NAFLD. [Display omitted]